A study on the perspectives of Barangay 60-A, Tacloban City residents on selected NGOs and GOs shelter damage classification schemes - Abarratigue, Cyrene Q.; Caspe, Jay Ryl P.; Dargantes, Arcelyn P.; de Veyra, Geraldine B. (2014)
This study looks into the perspectives of the Barangay 60-A residents regarding the shelter damage classification schemes used by selected INGOs and GOs. Through an interview schedule, the informants were asked about their perceptions, opinions and knowledge about the classification schemes utilized by selected INGOs and Gos in assessing the shelter damages brought by typhoon Yolanda.